Impact of Balkan and Banat Donkey Milk on the Technological Process, Microbiological Quality, Composition, and Consumer Acceptability of Rolled Cheese - Suzana Vidaković Knežević; Jelena Vranešević; Nenad Popov; Slobodan Knežević; Dragana Ljubojević Pelić; Milica Živkov Baloš (Foods, 2025)
Donkey milk is well known for its beneficial properties for human health, making it a valuable ingredient in the production of value-added cheese. Rolled cheese, a type of pasta filata cheese, is traditionally produced in the northern part of Serbia. In this study, we produced rolled cheese by adding a certain amount of donkey’s milk from the Balkan and Banat breeds to cow’s milk. The rolled cheese samples were analyzed for their microbiological quality, chemical composition, content of essential and trace elements, as well as sensory characteristics. Adding 10% and 20% donkey’s milk had no effect on the microbiological quality or hedonic scale of rolled cheeses compared with rolled cheese made from raw cow’s milk. However, the addition of donkey’s milk partially affected the chemical composition and mineral profile of the cheeses. The fat, fat in dry matter, calcium contents, and the ratio of calcium and phosphorus significantly (p < 0.05) decreased with the addition of donkey’s milk, while the ash, salt, sodium, and potassium contents significantly (p < 0.05) increased. The assessors successfully distinguished the rolled cheeses containing donkey’s milk from those made with cow’s milk, encouraging the future production of value-added cheese.